Gamification: A new approach to Ecuadorian education (Docentes 2.0 Journal, 2019)
This article aims to present the concept of Gamification as an alternative for education, considering it to be a relatively recent initiative. It is a phenomenon in the initial phase, lacking in further studies and discussions, but no less interesting, because it proposes a new approach to education and many other segments of contemporary human knowledge. This research shows us that in Ecuadorian Higher Education, as in other areas, its use is still incipient, because the controversy surrounding the issue is still considerable, however, it comes to combine efforts with other proposals of the same distance, in the attempt to magnify some of the learning problems of individuals, leading them to commitment and motivation in the educational environment. It is not a revolution, or proposal of abandonment of pre-existing concepts and procedures, but an attempt to compose what already exists and to take advantage of the benefits of evolution through which humanity passes so that learning becomes more and more natural to the eyes of individuals. The challenges will have to be relocated, may be technological, financial, procedural, educational or structural, with further studies and research and evaluation of the results can be assessed if the initiative is consistent and if it came to stay.
Keywords: Learning; education; gamification; educational technology